Monodisperse molecularly imprinted microsphere cartridges coupled with HPLC for selective analysis of dexamethasone and hydrocortisone in cosmetics by using matrix solid-phase dispersion. Issue 29 (9th July 2019) - Guo, Pengqi; Chen, Guoning; Shu, Hua; Li, Peng; Yu, Pei; Chang, Chun; Wang, Yitao; Fu, Qiang
Abstract : Monodisperse molecularly imprinted microspheres were used as the MSPD adsorbents for specific extraction of glucocorticoids in cosmetics. Abstract : The illegal addition of glucocorticoids to cosmetics can cause serious adverse reactions. For the selective determination of glucocorticoids in cosmetics, a simple, fast and sensitive method for the determination of dexamethasone and hydrocortisone has been developed by combining selective monodisperse molecularly imprinted microsphere matrix solid-phase dispersion and high performance liquid chromatography (MMIM-MSPD-HPLC). The prepared molecularly imprinted monodisperse microspheres have excellent specific affinity for dexamethasone and hydrocortisone and the obtained extract was thoroughly cleaned and can be directly subjected to HPLC for analysis without matrix interference. The established MMIM-MSPD-HPLC method was validated and successfully used for detecting dexamethasone and hydrocortisone in cosmetic samples with good selectivity, sensitivity and efficiency. The linear range was 0.05 to 50 μg g −1 with a limit of detection of 0.03 μg g −1 for dexamethasone and 0.02 μg g −1 for hydrocortisone, respectively. The RSD values of intra-day precision and inter-day precision are less than 6.52%. Compared with other literature methods, the established method has the advantages of accuracy, selectivity and specificity.